THE EFFECTS OF BRAND IMAGE, STORE ATMOSPHERE, AND PRODUCT QUALITY ON PURCHASING DECISIONS AT PANDA VAPESTORE - Kusdianto, Kusdianto; Siagian, Rahmad Putra; Muliati, Lisdewi (Dynamic Management Journal, 2024)
The purpose of this study was to determine the effect of brand image, store atmosphere, and product quality on purchasing decisions at Panda Vapesto, either partially or simultaneously. This study used a quantitative associative method with a quantitative approach, taking a sample of 67 people. Data collection techniques and tools are questionnaires or questionnaires. Descriptive analysis techniques are used to determine the description of respondents' answers and data distribution, while inferential statistical analysis is used to test hypotheses. Data processing was assisted by Microsoft Excel and SPSS software version 26. The results of this study showed 1) partially brand image had a positive and significant effect on purchasing decisions at Panda Vapestore as seen from the tcount 2.368 > ttable 1.98472 with a significance of 0.020 <0.05. 2) partially store atmosphere has a negative and significant effect on purchasing decisions at Panda Vapestore seen from the tcount -1.366 < ttable 1.98472 with a significance of 0.175 > 0.05. 3) partially, product quality has a positive and significant effect on purchasing decisions at Panda Vapestore. It is proven by the tcount value of 20,386 > ttable 1.98472 with a significance of 0.000 <0.05 4) simultaneously. brand image, store atmosphere, and product quality on purchasing decisions at Panda Vapestore alpha value of 5% (0.05), or fcount 161.602 > ftable 2.70.Key word: brand image, store atmosphere, product quality, andpurchasing decisions